(3LQGFe GdYfa GdLfSj aj HYV GdHdOGf GdYQHjI h SHd GdhbGjI efgG (B/ s - (3eUWai eSYhO EHQGgje CHhGdbGSes; (3eMehO eMeO SdjeGf cHjTs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2012)
(3ef NdGd JJHY eQGMd gPG GdHMK hLO Cf ef CNWQ GdeTcdGJ gj eTcdI GdYfa GdLfSj MjK Cf JaTj GdYfa GdLfSj aj Cj eLJeY dg YhGbH hNjeI Ydi GdeLJeY cGfJTGQ GdaSGO h GfgjGQ Gdbje h GdCNdGb h ZjQgG(B. (3h dPdc cGf dRGeB GdJfHjg Ydi LejY aFGJ GdeLJeY ef GdNWhQI GdcHQi ef JaTi eKd gPg GdLQGFe(B: (3h jJfGei NdGd gPG GdHMK GdJYQja Heaghe GdYfa GdLfSj Ydi eSJhi GdTQjYI GdESdGejI(B: (3h Ydi eSJhi GdbGfhf GdhVYj(B. (3cPdc Hjf GfJTGQ LQGFe GdYfa GdLfSj Ydi eSJhi HYV GdOhd GdYQHjI eOYheI HGdEMUGFjGJ h GdCQbGe GdJj MGhd Cf Jchf ObjbI bOQ GdeSJWGYs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj (B2012.s
(3HHdjhLQGajG(B: (3UaMGJ (B275-290.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdYfa GdLfSjs; (3Qcfi GdGZJUGHs; (3GdYhGed GdOGaYI dGfJTGQ GdYfa GdLfSis; (3JTQjY (B23 (3OjSeHQ (B1980s; (3hWA UZjQI GdSfs; (3GdYhGed GdfaSjIs; (3GdGSQIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs